2021
DOI: 10.1039/d1sc02885e
|View full text |Cite
|
Sign up to set email alerts
|

Multiple valence electron detachment following Auger decay of inner-shell vacancies in gas-phase DNA

Abstract: We have studied soft X-ray photoabsorption in the doubly deprotonated gas-phase oligonucleotide [dTGGGGT-2H]^2-. The dominating decay mechanism of the X-ray induced inner shell vacancy was found to be Auger decay...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 51 publications
(71 reference statements)
4
22
0
Order By: Relevance
“…More recent experiments have challenged this interpretation, as even in deprotonated gas-phase oligonucleotides, soft X-ray absorption predominantly produces B + and BH + fragments. 10 This finding suggests that B + fragments can originate from non-protonated sites and their formation then normally involves single H transfer, while BH + formation even requires double H transfer. To elucidate the underlying processes it is a straightforward strategy to measure the relative strength of single and double H-transfer processes in glycosidic bond-cleavage processes as a function of photon energy at all inner-shell absorption edges.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…More recent experiments have challenged this interpretation, as even in deprotonated gas-phase oligonucleotides, soft X-ray absorption predominantly produces B + and BH + fragments. 10 This finding suggests that B + fragments can originate from non-protonated sites and their formation then normally involves single H transfer, while BH + formation even requires double H transfer. To elucidate the underlying processes it is a straightforward strategy to measure the relative strength of single and double H-transfer processes in glycosidic bond-cleavage processes as a function of photon energy at all inner-shell absorption edges.…”
Section: Introductionmentioning
confidence: 99%
“…Therapeutic X-rays as well as fast ions used in radiotherapy efficiently induce inner shell excitations and ionizations, either directly in DNA or in surrounding water molecules. The resulting inner-shell vacancies are typically filled by Auger processes, leading to emission of energetic electrons which are of high 2 relevance for radiation damage [10]. Soft X-rays are an excellent to to create such inner-shell ionization and excitation proocesses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Wen et al experimentally [73] demonstrated, by monitoring the positive fragmentation patterns produced by absorption of soft X-ray and infrared photons, that the fragmentation of oligonucleotide dTGGGGT is not a direct consequence of the initial K-shell vacancy but it is rather due to the multiple detachment of valence electrons following the relaxation of the K-shell vacancy. 1.…”
Section: Near-edge Soft X-ray Absorption Mass Spectrometrymentioning
confidence: 99%